THE EFFECT OF LED MAGNETIC ON STAPHYLOCOCCUS AUREUS BACTERIA - Yonatan; Astuti, Suryani Dyah; Ain, Khusnul; Arifianto, Deni; Yaqubi, Ahmad Khalil (Universitas Airlangga, 2025)
Nosocomial infections, caused by viruses, bacteria, and fungal pathogens, often occur during treatment in health facilities due to cross-contamination from healthcare workers or medical equipment. The study explores the efficacy of static magnetic fields and photodynamic inactivation in inactivating Staphylococcus aureus bacteria, a crucial step in sterilization. The study used high-power blue LEDs and static magnetic fields generated by neodymium magnets. The highest reduction percentage observed was 81.92 ± 7.92%, found in the combination treatment of static magnetic fields (SMF) with LED illumination at the F8 microplate location, with a treatment time of 40 minutes, an LED dose of 11.72 J/cm², and a magnetic field dose of 25.61 mT. The lowest reduction percentage, 52.41 ± 7.64%, was observed at the F8 microplate location with a treatment time of 10 minutes, an LED dose of 2.93 J/cm², and a magnetic field dose of 25.61 mT.